2021
DOI: 10.1007/s11695-020-05196-7
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Obese Patients: a UK Population Analysis

Abstract: Background Obstructive sleep apnea (OSA) is an increasingly common disorder associated with increased cardiovascular disease, mortality, reduced productivity, and an increased risk of road traffic accidents. A significant proportion of patients with OSA in the UK are undiagnosed. This study aims to identify risk factors for OSA in an obese cohort. Method A population-based study was conducted of obese patients (BMI ≥ 30 kg/m2) from the Clinical Practice Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 36 publications
3
24
1
Order By: Relevance
“…It is reported that OSA is more common medical condition in obese people because of narrowing of the upper respiratory muscles occurs due to the accumulation of adipose tissue (Erridge et al, 2021). Li et al (2020) in their review study that examined the relationship between serum vitamin D levels and OSA disorder concluded that this disorder may be associated with low serum levels of this vitamin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that OSA is more common medical condition in obese people because of narrowing of the upper respiratory muscles occurs due to the accumulation of adipose tissue (Erridge et al, 2021). Li et al (2020) in their review study that examined the relationship between serum vitamin D levels and OSA disorder concluded that this disorder may be associated with low serum levels of this vitamin.…”
Section: Discussionmentioning
confidence: 99%
“…Two common sleep-related disorders include Obstructive Sleep Apnea (OSA) and Restless Legs Syndrome (RLS) (Lee et al, 2019). OSA is a more common medical condition in obese people (Erridge et al, 2021) that varies in severity depending on the number of apnea and hypopnea interruptions per hour and is measured by overnight Polysomnogram (PSG). This condition can have a significant impact on a person's daily lifestyle, as it can cause drowsiness during the day, headaches, difficulty concentrating, or hyperactivity in children.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a higher incidence of obstructive sleep apnea (OSA) in obese patients. [ 2 ] All these factors contribute to a decreased respiratory reserve and an increased risk of peri-operative respiratory events in morbidly obese patients. The presence of difficult airways also mandates the practice of rapid sequence induction in these population groups.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has reached epidemic proportions globally; with lifestyle modifications not proving to be long-lasting and as pharmacological options are limited by high cost, adverse effects, modest efficacy, and hesitancy by patients and clinicians, surgery is currently the main, widely used course of treatment for patients with severe obesity . Bariatric surgery allows patients to lose weight quickly, and, in many cases, resolve, or at least improve, obesity-related comorbidities. It is also associated with increased long-term survival. , Yet, several complications may arise that require general practitioners’ awareness and expertise. , Among them, malabsorption of nutrients is routinely followed and treated accordingly, while altered absorption/pharmacokinetics of orally administered drugs is oftentimes overlooked …”
Section: Introductionmentioning
confidence: 99%